"It's Everyone's iPad": Tablet use in a play-based preschool classroom. (June 2021) - Fantozzi, Victoria B
Although existing literature has established that technologies are utilized in play and can be supportive of learning, utilization of technologies in play-based classrooms is not commonplace. This study is an holistic examination of a successful 2-year process of integrating an iPad into a play-based preschool setting. Each year the use of the iPad increased, demonstrating its applicability in a play-based environment. This study adds to the existing research base by examining the confluence of actors in a play-based setting. As the iPad became a part of the classroom, new practices began to emerge as the children, teachers, and families began using it for their own purposes.